Robust anti-nociceptive effects of MAG lipase inhibition in a model of osteoarthritis pain - Burston, James J.; Mapp, Paul I.; Sarmad, Sarir; Barrett, David A.; Niphakis, Micah J.; Cravatt, Benjamin F.; Walsh, David A.; Chapman, Victoria (Wiley, 2016)
BACKGROUND AND PURPOSE: Chronic pain is often a symptom of knee osteoarthritis (OA) for which current analgesics are either inadequate, or are associated with serious side effects. The endocannabinoid system may offer alternative targets for pain-relief. We evaluated the effects of a potent and selective MAG lipase inhibitor (MJN110) on OA pain behaviour, spinal mechanisms of action and joint histopathology in the rat. Experimental approach: Intra-articular injection of monosodium iodoacetate (MIA) models OA pain and mimics clinical joint pathology. Effects of MJN110 on MIA-induced weight bearing asymmetry and lowered paw withdrawal thresholds (PWTs), changes in spinal gene expression and brain levels of relevant lipids were determined. Key results: Acute MJN110 (5 mg·kg−1) significantly reversed MIA induced weight bearing asymmetry (MIA /vehicle: 68 ± 6g; MIA /MJN110: 35 ± 4g, p<0.05) and lowered ipsilateral PWTs (MIA /vehicle: 7 ± 0.8g; MIA /MJN110: 11 ± 0.6g, p<0.05), via both CB1 and CB2 receptors. Repeated treatment with MJN110 (5 mg·kg−1) resulted in anti-nociceptive tolerance. A lower dose of MJN110 (1 mg·kg−1) acutely inhibited pain behaviour, which was maintained for one week of repeated administration, but had no effect on joint histology. MJN110 significantly inhibited expression of MPGES1 (p<0.05) in the ipsilateral dorsal horn of the spinal cord of MIA rats, compared to vehicle treated MIA rats. Both doses of MJN110 significantly elevated brain levels of the endocannabinoid 2-AG. Conclusions and Implications: Our data support the further investigation of the therapeutic potential of MAG lipase inhibitors for the treatment of OA pain.